Investasikan Masa Depanmu Dengan Pendidikan Dan Skill Pembekalan Pentingnya Investasi Pendidikan Bagi Siswa SMA Agus Salim Semarang - Tjandra Tirtono; Triani Triani; Nurdhiana Nurdhiana (BADAN PENERBIT STIEPARI PRESS, 2023)
This community service is a way to open up views that investment is not just about funds or money and the like, but education is also a very promising investment. Education is also an investment in the future which includes 3 components of character education, competency and literacy. If someone invests in education, it is possible that they will have a good future. Several things make education an important investment in life. Firstly, character, it is recognized worldwide that education can create independence. There are two types of character, namely moral character and performance character. These two competencies are able to encourage someone to think critically, creatively, communicatively, and be able to work together. Third is literacy. Literacy is a person's ability to process and understand information when carrying out the process of reading and writing. Education can direct human resources to have broad insight. For this reason, it is necessary to motivate the younger generation, especially high school students, to continue their education to a higher level.